Taking the Ombudsman Concept into the Private Sector: Notes on the Banking Ombudsman Scheme in New Zealand - Tollemache, Nadja (Victoria University of Wellington Law Review, 1996)
This article traces the development of the institution of Ombudsman in New Zealand and comments on the move of the idea from the public to the private sector. The article first discusses the historical tests for unlawfulness under the Ombudsmen Act 1962 and 1975, which focused on the public sector. The success of the Ombudsmen in the public sector then led to the appointment of New Zealand's first Banking Ombudsman in 1992, modelled on similar offices in the United Kingdom and Australia. However, the article discusses factors that distinguish New Zealand's Banking Ombudsman to that of the United Kingdom: the sequence of events, the structure of the office, and the relationship between the Parliamentary Ombudsman and those in the private sector. *Note: a French language summary of this article is provided at 244.